Tensile and Buckling Analysis of Polymeric Composite Columns - Oleiwi, Jawad Kadhim; hassani, Emad Saadi Al-; Mohammed, Alaa Abd (Basrah Journal for Engineering Sciences, 2014)
This research studied the critical load of composite columns theoretical and numerical by using ANSYS14 package depended on experimental tensile properties of composite specimens. The composite specimens were prepared by hand lay-up technique made from unsaturated polyester reinforced with glass fibers with different fiber volume fraction V f , aspect ratio (L/T), and angle of fibers for coarse and fine woven fibers. The critical load that obtained by using program (ANSYS 14) have also shown a good agreement with results that were obtained theoretically and the maximum difference was (0.7%). The results show that the maximum value of the critical load can be observed at V f =11%, L/T = (3.5) and θ = (0 º /90 º ) for fine woven fibers was (622.115N). Also its found the maximum critical load for coarse woven fibers can be observed at V f %=8%, L/T=(3.5) and θ = (0 º /90 º ) was (486.887N). Also the observed values of tensile properties and predicated values are scattered close to the (45 ˚ ) line.